An artificial foot for prosthesing invalids - Vatolinskiy, Leonid; Lukovenko, Oleksandr; Khmelevskaya, Iryna; Shchetinina, Lyubov; Belevtsova, Lyudmila (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The designed constructions of foot prosthesis by Chopart and shin ones by Pirogov and Syme with the use of whole-piece feet of the foot-forefoot type or Pirogov foot do not make it possible to fully satisfy patients’ demands with a high degree of motor activity. In order to increase the efficacy of rehabilitation of invalids with a high degree of motor activity, an artificial foot was designed for foot prostheses by Chopart and Lisfrank and shin ones by Pirogov and Syme; it is a resilient element made of a composite material, to which a prosthesis sleeve is attached. A possibility to dose out the rigidity along the element ensures the spring and shock-absorbing functions of the foot, as well as its effective roll-over along a support. The designed constructions of foot prosthesis by Chopart and shin ones by Pirogov and Syme with the use of resilient composite elements make it possible to improve the prosthetic-orthopaedic provision of the disabled with a high degree of motor activity. Biomechanical and clinical studies gave an objective assessment of the obtained results, demonstrated a higher quality of walking and its better biomechanical characteristics.